Chronic kidney disease and risk of atrial fibrillation and heart failure in general population-based cohorts – the BiomarCaRE project. (14th October 2021) - Rehm, M; Rothenbacher, D; Iacoviello, L; Costanzo, S; Tunstall-Pedoe, H; Fitton, C.A; Soederberg, S; Hultdin, J; Salomaa, V; Palosaari, T; Waldeyer, C; Schnabel, R.B; et al.
Abstract: Background: Chronic kidney disease (CKD) has a complicated relationship with the heart, leading to many adverse outcomes. Purpose: The aim of the study was to evaluate the relationship between CKD and the incidence of atrial fibrillation (AF) and heart failure (HF) along with mortality as a competing risk in general population cohorts. Methods: This study was conducted as part of the BiomarCaRE project using harmonised data from 12 population-based cohorts (n=40, 212) from Europe. Cox proportional hazards models were used to determine hazard ratios (HRs) for the incidence of AF and HF in CKD and with competing mortality risk after adjusting for covariates. Results: Mean age at baseline was 51.1 (standard deviation 11.9) years, and 49.3% were men. Overall, 3.5% had CKD at baseline. The rate for incident AF was 3.9 per 1000 person-years during follow-up. The HR for AF for those with CKD compared with those without was 1.23 (95% CI 1.00–1.52, p=0.0465) after adjustment for covariates. The rate for incident HF was 3.9 per 1000 person-years and the associated risk in the presence of CKD was HR 1.67 (95% CI 1.39–2.01). In subjects with CKD, N-terminal pro-B-type natriuretic peptide (NT-proBNP) showed an association with AF, while NT-proBNP and C-reactive protein (CRP) showed an association with HF. Conclusion: CKD is an independent risk factor for subsequent AF and even more so for HF. In patients with CKD, NT-proBNP was clearly associated with subsequent risk of AF. In addition to this marker, hs-CRP was also associated with risk of subsequent HF. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): 7th framework programme collaborative project, grant agreement no. HEALTH-F2-2011_278913.